Effets de la consanguinité sur les performances de croissance et de viabilité des ovins des races Timahdite et Sardi - Abderrahmane JANNOUNE; Ismaïl BOUJENANE; Mohammed FALAKI; Lahsen DERQAOUI (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2014)
The objective of this study was to assess the effect of inbreeding on weights at 10 (W10d), 30 (W30d) and 70 days of age (W70 d), on average daily gain between 10-30 days (ADG10-30) and between 30-70 days (ADG30-70), as well as on the lamb survival between birth and 70 days of Timahdite and Sardi sheep. The study was based on the performance of 183086 Timahdite lambs and 46193 Sardi lambs collected from 2002 to 2012 in selection farms supervised by the National Association of Sheep and Goats. Effects of inbreeding on performance were estimated by least-squares method. The increase by 1% in the level of individual inbreeding leads to a significant decrease of 0.0022 and 0.0023 kg for W30d and W70d, respectively of Timahdite lambs and 0.0044 and 0.0065 kg, respectively of Sardi lambs. The effect of inbreeding was non-significant on W10d and ADG of both breeds. However, the effect was significantly positive (0.0283%/%F) on Timahdite lamb survival and positive but not significant (0.0216%/%F) on Sardi lamb survival. Maternal inbreeding had a significant effect (0.0366 g/j/%F) only on the ADG30-70 of Timahdite breed. It was concluded that inbreeding depression has little significance on flocks with a low level of inbreeding.